Principal Accountability In Enhancing The Quality Of Islamic Religious Education Instruction: A Qualitative Study At SMK-S Al-Inayah - Ratu Candra Nur Aulia; Muttaqin; Wiwin Narti; Novita Nurul Hidayah; Mabruri (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
Sustained efforts to elevate the quality of Islamic Religious Education (IRE) in vocational secondary schools depend critically on the managerial accountability exercised by the school principal, yet most Indonesian studies still treat principal accountability as an administrative checklist rather than as an instructional driver linked to specific subject domains. This study examines how principal accountability operates as an integrated mechanism of planning, supervision, evaluation, and culture-building that shapes the quality of IRE instruction at SMK-S Al-Inayah, Rimbo Bujang, Jambi Province, Indonesia. A qualitative case-study design was employed, with informants selected purposively, comprising one principal, one IRE coordinator-teacher, and one twelfth-grade student. Data were generated through non-participant classroom observation across four sessions, three semi-structured interviews of 45–60 minutes each, and documentary analysis of school work plans, supervision records, and learning achievement reports. Analysis followed the Miles, Huberman, and Saldaña model, and trustworthiness was established through source and method triangulation and member checking. The findings reveal that principal accountability is enacted through six concrete practices: setting competence standards, supervising instruction, evaluating learning outcomes, facilitating teacher professional development, partnering with parents, and producing periodic performance reports. Instructional quality is perceived along three dimensions: innovative methods, character formation, and management-curriculum alignment. The principal’s role is distributed across the planning, implementation, and evaluation phases of the instructional cycle, indicating that accountability functions less as bureaucratic compliance and more as instructional leadership. The study concludes that subject-specific, cyclical, and culture-embedded accountability is a feasible model for strengthening IRE quality in private vocational schools.